1998
DOI: 10.1017/s0048577298970615
|View full text |Cite
|
Sign up to set email alerts
|

Motor programming of response force and movement direction

Abstract: Effects of movement advance information were assessed on the prestimulus amplitude of the lateralized readiness potential~LRP!, on the contingent negative variation~CNV!, and on reaction time~RT!. In a precuing paradigm with movement parameters hand, direction, and force, partial precues provided advance information about either hand alone, hand plus force, or hand plus direction, and the full precue specified all response parameters. The full precue produced the shortest RTs and the largest CNV amplitude, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
96
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(118 citation statements)
references
References 20 publications
21
96
1
Order By: Relevance
“…As already described in healthy controls [50,51], the CNV amplitude was larger for the more informative spatial cue (alerting and orienting, temporally and spatially informative) compared to the less informative center cue (alerting, temporally informative) and noninformative cue. Quantitatively, its amplitude did not differ between sd-dMCI and the other two MCI subgroups suggesting that the functionality of the attentional networks was not modulated according to the predominance of dysexecutive deficits.…”
Section: Discussionsupporting
confidence: 73%
“…As already described in healthy controls [50,51], the CNV amplitude was larger for the more informative spatial cue (alerting and orienting, temporally and spatially informative) compared to the less informative center cue (alerting, temporally informative) and noninformative cue. Quantitatively, its amplitude did not differ between sd-dMCI and the other two MCI subgroups suggesting that the functionality of the attentional networks was not modulated according to the predominance of dysexecutive deficits.…”
Section: Discussionsupporting
confidence: 73%
“…In recent years scientists have utilized neuroimaging techniques in an attempt to distinguish between possible perceptual/cognitive and motor effects of advance information on movement initiation (i.e., RT). For example, Ulrich et al (1998) reported that when the response hand was precued there was greater activity over the contralateral hemisphere. This relative increase in activity is known as the lateralized readiness potential (LRP), which is an electrophysiological index of selective hand activation in the primary motor cortex (Osman et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Although processes related to attention for the upcoming stimulus also contribute to CNV (Brunia, 1993;Van Boxtel, 1994), the late CNV is a sensitive index of the accumulated motor activation. For example, Ulrich et al (1998) showed that the amplitude of the late CNV increased with the amount of response information communicated by S1.…”
Section: Activationmentioning
confidence: 99%